Development of physical and skill training drill prescription systems for elite Australian Rules football - Corbett, D. M.; Bartlett, J. D.; O`connor, F.; Back, N.; Torres-Ronda, L.; Robertson, S. (Science and Medicine in Football, 2018)
Objectives: To develop three different training drill classification systems for Australian Rules football using physical and skill-related data. Methods: Forty professional Australian footballers wore 10 Hz Global Positioning System units for six matches and 17 training sessions including 35 drills. High intensity running per minute, metres per minute and high-intensity running as a percentage of total distance were obtained to represent each drill's physical requirements. Velocity at kick (moving or stationary), time in possession (greater or less than 2 s) and the presence of pressure were coded for each kick to represent the constraints associated with each drill. Results: For the first system, two k-means clustering algorithms were run on physical and skill data separately to identify similarities between drills. For the second system, z-scores were calculated for each physical and skill characteristic to allow direct comparison of each drill with match conditions. For the third system, a "Specificity Index" was calculated using the absolute average of pooled z-scores for physical and skilled characteristics. Conclusions: The three systems developed in this study can be used to aid training prescription in elite Australian Rules football.